Genome-wide identification and analyses of cotton high-affinity nitrate transporter 2 family genes and their responses to stress - Pu, Yuanchun; Wang, Peilin; Abbas, Mubashir; Khan, Muhammad Aamir; Xu, Jiangling; Yang, Yejun; Zhou, Ting; Zheng, Kai; Chen, Quanjia; Sun, Guoqing (Frontiers in Plant Science, 2023)
Nitrate transporters (NRTs) are crucial for the uptake, use, and storage of nitrogen by plants. In this study, 42 members of the GhNRT2 (Nitrate Transporter 2 family) were found in the four different cotton species. The conserved domains, phylogenetic relationships, physicochemical properties, subcellular localization, conserved motifs, gene structure, cis-acting elements, and promoter region expression patterns of these 42 members were analyzed. The findings indicate that the domain of NRT2 is typical. Subcellular localization tests have confirmed that they are hydrophobic proteins that are mostly located on the cytoplasmic membrane. The NRT2 family of genes with Arabidopsis and rice underwent phylogenetic analysis, and the results revealed that GhNRT2 could be divided into three groups. The same taxa also shared similar gene structure and motif distribution. The composition of cis-acting elements suggests that most of the expression of GhNRT2 may be related to plant hormones, abiotic stress, and photoreactions. The GhNRT2 gene is highly expressed, mainly in roots. Drought, salt, and extreme temperature stress showed that GhNRT2 gene expression was significantly up-regulated or down-regulated, indicating that it may be involved in the stress response of cotton. In general, the genes of the NRT2 family of cotton were comprehensively analyzed, and their potential nitrogen uptake and utilization functions in cotton were preliminarily predicted, and an experimental basis was provided for the adverse stress in which they may contribute.